The Role of Information Technology in Zakat Management at the National Zakat Collection Agency - Rahmani; Khusnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Although technology and information in Indonesia have been widely used in various aspects such as zakat management, it is known that there are still obstacles during implementation. The obstacles faced include low public awareness in knowing about the use of technology in the process of managing zakat, the lack trained human resources in managing information technology systems, especially in the field of zakat, and limited technological infrastructure in certain areas. The purpose of this writing is to provide an analysis of the role of information technology in managing zakat at the national zakat collection agency. The writing method uses a qualitative type. The results and conclusions drawn are that Baznas (National Zakat Collection Agency) in distributing, managing, or collecting zakat can be assisted by the existence of technology such as AI, IoT etc. In managing zakat, Baznas uses two types of software, namely SIMBA (Baznas Information Management System, in this application, financial report printing, distribution and operations, zakat collection, muzakki and mustahik management will presented. Second software used by Baznas is ERP (Enterprise Resource Planning) intended for Baznas in managing finances through cooperation with Financial Information System.